2020
DOI: 10.3390/nu12061555
|View full text |Cite
|
Sign up to set email alerts
|

Association between Non-Alcoholic Fatty Liver Disease and Dietary Habits, Stress, and Health-Related Quality of Life in Korean Adults

Abstract: Considering the increasing prevalence of non-alcoholic fatty liver disease (NAFLD), this study aimed to evaluate the association between NAFLD and dietary habits, stress, and health-related quality of life (HRQoL) in Korean individuals by using data from the Korea National Health and Nutrition Examination Survey (KNHANES) VI 2013–2015. NAFLD was defined in individuals with a hepatic steatosis index (HSI) value ≥36. Eating habits were assessed based on the frequencies of eating and eating out; stress was assess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 65 publications
0
19
1
1
Order By: Relevance
“…The background of liver fibrosis involves multiple processes, including alcoholic lesions, chronic forms of viral hepatitis, and metabolic syndrome, which is becoming one of the most important causes today, a burden on our society. Western diets, reduced physical activity, and constant stress all actively contribute to the dramatic increase in nonalcoholic steato-hepatitis (NASH) prevalence ( 3 , 4 ).…”
Section: Introductionmentioning
confidence: 99%
“…The background of liver fibrosis involves multiple processes, including alcoholic lesions, chronic forms of viral hepatitis, and metabolic syndrome, which is becoming one of the most important causes today, a burden on our society. Western diets, reduced physical activity, and constant stress all actively contribute to the dramatic increase in nonalcoholic steato-hepatitis (NASH) prevalence ( 3 , 4 ).…”
Section: Introductionmentioning
confidence: 99%
“…In this study, HRQoL was assessed by the EuroQol-5D (EQ-5D) instrument, which measures/comprises of five dimensions, namely, mobility, self-care, usual activities, pain/ discomfort, and anxiety/depression. This study showed that a decrease in the EQ-5D score by one unit was associated with increased risk of NAFLD by more than threefold, raising the awareness of considering HRQoL in the context of NAFLD [58].…”
Section: Hrqol and Nafldmentioning
confidence: 75%
“…Notably, in exploring correlations between NAFLD, dietary habits, stress, and HRQoL in Korean individuals, Han [58] identified a 1.3-fold increase in the risk of NAFLD in individuals with increased perceived stress, suggesting that stress management should be included in the treatment of NAFLD [58]. Furthermore, a large cross-sectional study involving 171,321 apparently healthy Korean adults identified an independent association between higher levels of perceived stress and a higher prevalence of NAFLD [56].…”
Section: Chronic Psychosocial Stress and Nafldmentioning
confidence: 99%
See 2 more Smart Citations